siRNA-mediated inhibition of hTERT enhances the effects of curcumin in promoting cell death in precursor-B acute lymphoblastic leukemia cells: an in silico and in vitro study - Muhammad Hossein Ashoub; Ali Afgar; Alireza Farsinejad; Razieh Razavi; Samira Anvari; Ahmad Fatemi (Scientific Reports)
Abstract This study investigates the interrelationship between human telomerase reverse transcriptase (hTERT) and ferroptosis in precursor-B (pre-B) acute lymphoblastic leukemia (ALL), specifically examining how hTERT modulation affects ferroptotic cell death pathways. Given that hTERT overexpression characterizes various cancer phenotypes and elevated telomerase activity is observed in early-stage and relapsed ALL, we investigated the molecular mechanisms linking hTERT regulation and ferroptosis in leukemia cells. The experimental design employed Nalm-6 and REH cell lines under three distinct conditions: curcumin treatment, hTERT siRNA knockdown, and their combination. Cell viability and proliferation were assessed via MTT and BrdU assays at 24- and 48-hour intervals post-treatment. Ferroptotic and oxidative markers were quantified using commercial assays, while cell death parameters and gene expression were evaluated through flow cytometry and qRT-PCR analyses. Molecular docking studies were performed to evaluate protein-ligand interactions. Results demonstrated that combined curcumin treatment and hTERT knockdown significantly enhanced cytotoxicity in Nalm-6 cells compared to individual interventions. This was characterized by the upregulation of ferroptosis promoters (lipid-ROS, Fe²⁺, ACSL4) and suppression of inhibitors (GSH, GPx, SLC7A11, GPx4). The response showed cell-line specificity, with Nalm-6 cells exhibiting enhanced ferroptotic sensitivity while REH cells underwent apoptotic cell death. Molecular docking revealed strong curcumin-protein interactions (∆G = -34.24 kcal/mol for hTERT). This study establishes hTERT as a critical regulator of ferroptotic cell death in pre-B ALL, operating through redox homeostasis, iron metabolism, and lipid peroxidation pathways. The cell-type-specific responses suggest promising therapeutic strategies through combined hTERT suppression and ferroptosis induction.